Potential Pharmacological Effects of Ethanolic Extract of Annona Muricata l. Leaves in Animal Models - Chan, Pit Foong (2011)
Annona muricata L, locally known as “durian belanda” has been used in folklore medicine to treat fever, cough, diarrhea, sedative, rash, ring worm and lactation for women afterbirth. The aims of this study were to investigate the anti-inflammatory, anti-nociceptive and anti-ulcerogenic activities and the mechanisms involve of the ethanolic leaves extract of Annona muricata L (EEAM) in various animal models. The anti-inflammatory effects of EEAM were tested against xylene-induced ear edema in mice and complete Freund’s adjuvant (CFA)-induced arthritis in rats. Anti-nociceptive activity of EEAM was evaluated using acetic acid-induced abdominal writhing in mice, formalin test in rats and hot plate test in mice. Furthermore, the anti-ulcerogenic effect of EEAM was studied in ethanol-induced ulcer model in rats, ethanol-induced gastric lesions in N-Nitro-L-arginine methyl ester hydrochloride (L-NAME)-pre-treated rats as well as ethanol-induced gastric lesions in N-ethylmaleimide (NEM)-pre-treated rats test model to determine its mechanism. LD50 of EEAM was found to be 890 mg/kg when screened for its toxicity. At 100 and 300 mg/kg orally, EEAM produced significant dose-dependent inhibition in xylene-induced ear edema in mice by 63.10 and 72.41%, respectively. In CFA-induced arthritis model, administration of EEAM at the highest dose of 100 mg/kg significantly attenuated the development of swelling by 86.07%. Furthermore, at the similar dose i.e. 100 mg/kg EEAM also significantly suppressed the release of IL-1β and TNF-α in local arthritic tissue in ELISA test by inhibition of 43.06 and 46.37%, respectively. Effects produced by EEAM were significantly higher than those produced by indomethacin (10 mg/kg, p.o.) in inhibiting both cytokines in the CFA-induced arthritis model by 41.67 and 37.27%, respectively. For anti-nociceptive effect, the inhibition in the acetic acid-induced writhing test produced by both 100 (53.04%) and 300 mg/kg (95.30%) of EEAM were greater than that produced by 20 mg/kg of indomethacin (55.44%). Experimental evidence obtained in this study indicates that EEAM significantly reduced acetic acid-induced writhes in mice and the formalin-induced paw licking in rats dose-dependently. Administration of EEAM at 300 mg/kg (66.21%) exhibited significant and comparable anti-nociceptive activity with acetylsalicylic acid (ASA) (64.35%) in the formalin test. EEAM at 100 and 300 mg/kg also increased the latency time of mice exposed to the hot plate. Based on the results shown, we suggested that its anti-nociceptive effect may be mediated via both peripheral and central mechanisms. This has been supported by findings in a nociceptive study with pretreatment of naxolone. Results showed that there is also a possibility of the involvement of opioid mechanism in the effect of EEAM. EEAM decreased the ulcerative lesion produced by ethanol in rats in a dose-dependent manner. EEAM at 30 mg/kg exhibited an inhibitory effect by 51.77%, which is slightly greater than the effect of lansoprazole by 46.95%. The prior administration of L-NAME, a NO-synthase inhibitor, did not reduce the anti-ulcerogenic effect of EEAM in ethanol-induced ulcer model, suggesting that there is no participation of nitric oxide (NO) in its pharmacological mechanism. Pre-treatment with NEM, a thiol blocker, including mucosal non-protein sulfhydryl groups, reduced the anti-ulcerogenic effect of EEAM in the same ulcer model. For histology study, inflammatory features which consist of edema, congestion, hemorrhage and necrosis were investigated. EEAM at all doses showed significant histological changes excluding the features in edema. As a conclusion, EEAM possesses anti-inflammatory, anti-nociceptive and anti-ulcerogenic effects.